The component structure of teacher-musician’s moral aesthetic activity - Rakityanskaya, L.M. (Pedagogy of Higher and Secondary Education, 2006)
In the article, the structure, the topical ness, and the criterions of the formed moral-aesthetic activity of teacher-musician are considered.